British Association of Dermatologists' guidelines for the investigation and management of generalized pruritus in adults without an underlying dermatosis, 2018. (22nd January 2018) - Millington, G.W.M.; Collins, A.; Lovell, C.R.; Leslie, T.A.; Yong, A.S.W.; Morgan, J.D.; Ajithkumar, T.; Andrews, M.J.; Rushbook, S.M.; Coelho, R.R.; Catten, S.J.; Lee, K.Y.C.; et al.
Abstract : Plain language summary available online